The peacemaker story : the emu, brolga and jabiru - Rosendale, George; Saunders, Zane.; Paterson, Janine; Wontulp-Bi-Buya College (North Cairns, Qld. : Wontulp-Bi-Buya College, 2000)
Dreaming story for children about making peace.
Cover title.
Includes 4 sheets of classroom activities.
Sponsored by "Engaging Australia Funding Programme"--Back cover.
Keywords: Friendship in children -- Juvenile literature; Aboriginal Australians -- Folklore; Religions - Christianity; Stories and motifs - Birds; Religion - Dreaming - Birds; Stories and motifs - Brolga; Religion - Dreaming - Birds - Emu